The evolution of lateral dose distributions of helium ion beams in air: from measurement and modeling to their Impact on treatment planning - Besuglow, Judith; Tessonnier, Thomas; Kopp, Benedikt; Mein, Stewart; Mairani, Andrea (Frontiers in physics, 2022)
To start clinical trials with the first clinical treatment planning system supporting raster-scanned helium ion therapy, a comprehensive database of beam characteristics and parameters was required for treatment room-specific beam physics modeling at the Heidelberg Ion-Beam Therapy Center (HIT). At six different positions in the air gap along the beam axis, lateral beam profiles were systematically measured for 14 initial beam energies covering the full range of available energies at HIT. The 2D-array of liquid-filled ionization chambers OCTAVIUS from PTW was irradiated by a pencil beam focused at the central axis. With a full geometric representation of HIT’s monitoring chambers and beamline elements in FLUKA, our Monte Carlo beam model matches the measured lateral beam profiles. A second set of measurements with the detector placed in a water tank was used to validate the adjustments of the initial beam parameters assumed in the FLUKA simulation. With a deviation between simulated and measured profiles below ±0.8 mm for all investigated beam energies, the simulated profiles build part of the database for the first clinical treatment planning system for helium ions. The evolution of beamwidth was also compared to similar simulations of the clinically available proton and carbon beam. This allows a choice of treatment modality based on quantitative estimates of the physical beam properties. Finally, we investigated the influence of beamwidth variation on patient treatment plans in order to estimate the relevance and necessary precision limits for lateral beam width models.
Gesehen am 01.03.2022